Generated covariates in nonparametric estimation: a short review - Mammen, Enno; Rothe, Christoph; Schienle, Melanie (Recent Developments in Modeling and Applications in Statistics, 2013)
In many applications, covariates are not observed but have to be estimated from data. We outline some regression-type models where such a situation occurs and discuss estimation of the regression function in this context. We review theoretical results on how asymptotic properties of nonparametric estimators differ in the presence of generated covariates from the standard case where all covariates are observed. These results also extend to settings where the focus of interest is on average functionals of the regression function.